Pengaruh Self Efficacy, Pengetahuan Perpajakan, Pertimbangan Pasar Kerja, dan Pengaruh Orang Tua terhadap Minat Karir Mahasiswa Akuntansi menjadi Konsultan Pajak - Susanti, Dina; Robinson (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research examines the influence of self-efficacy, tax knowledge, labor market considerations, and parental impact on accounting students' interest in becoming tax consultants. The research sample comprises 224 accounting students from Bengkulu University, Muhammadiyah Bengkulu University, Dehasen University, and UNIHAZ who have taken taxation courses. The primary data was collected using a questionnaire distributed via Google Forms. Data were analyzed using the Statistical Program for Social Science (SPSS) 26. The study results indicate that self-efficacy does not have a significant partial effect on the career interest of accounting students in becoming tax consultants. Meanwhile, tax knowledge, labor market considerations, and parental influence partially have a positive and significant effect on accounting students' career interest in becoming tax consultants. However, self-efficacy, tax knowledge, labor market considerations, and stimulant parental influence, as stimulants affect the career interest of accounting students in becoming tax consultants.